COVID-19 in 28-Week Triplets Caused by Intrauterine Transmission of SARS-CoV-2—Case Report - Disse, Sigrid C.; Manuylova, Tatiana; Adam, Klaus; Lechler, Annette; Zant, Robert; Klingel, Karin; Aepinus, Christian; Finkenzeller, Thomas; Wellmann, Sven; Schneble, Fritz (Frontiers in Pediatrics, 2021)
Since the beginning of the COVID-19 pandemic, in-utero transmission of SARS-CoV-2 remains a rarity and only very few cases have been proven across the world. Here we depict the clinical, laboratory and radiologic findings of preterm triplets born at 28 6/7 weeks to a mother who contracted COVID-19 just one week before delivery. The triplets showed SARS-CoV-2 positivity right after birth, developed significant leukopenia and early-onset pulmonary interstitial emphysema. The most severely affected triplet I required ten days of high-frequency oscillatory ventilation due to failure of conventional invasive ventilation, and circulatory support for four days. Despite a severe clinical course in two triplets (triplet I and III), clinical management without experimental, targeted antiviral drugs was successful. At discharge home, the triplets showed no signs of neurologic or pulmonary sequelae. Placental immunohistology with SARS-CoV-2 N-protein localized strongly to syncytiotrophoblast cells and to fetal Hofbauer cells proved intrauterine virus transmission. We discuss the role of maternal viremia as a potential risk factor for vertical transmission. To the best of knowledge, our report presents the earliest unequivocally confirmed prenatal virus transmission in long-term surviving children, i.e. at the beginning of the third trimester.